Frequency of Factors Leading To Intrapartum Perineal Tears in Primigravida - Rukh, Mah; Farhad, Umaiyma; Khan, Sadia; Shafiq, Sanam; Faiz, Sidra; khan, Saira (Biological and Clinical Sciences Research Journal, 2025)
Intrapartum perineal tears are common complications during childbirth, particularly in primigravida women. Several factors, including episiotomy, vacuum-assisted delivery, and fetal macrosomia, influence the occurrence of these tears. This study aimed to evaluate the frequency and associated factors leading to intrapartum perineal tears in primigravida women in a hospital setting in Peshawar, Pakistan. Objective: To evaluate the frequency and associated factors leading to intrapartum perineal tears in primigravida women in a hospital setting in Peshawar, Pakistan Methods: This cross-sectional study was conducted at the Department of Obstetrics and Gynaecology, Hayatabad Medical Complex, Peshawar, from 15th January 2021 to 15th July 2021. A total of 123 primigravida women with singleton pregnancies were included in the study. The sample size was calculated using the WHO sample size calculator with a 95% confidence interval and a 7% margin of error. Participants were selected using non-probability consecutive sampling. Demographic data and information on episiotomy, vacuum delivery, and macrosomia were collected through a structured proforma. Data were analyzed using SPSS version 22, and descriptive statistics and chi-square tests were used to identify associations. Results: The mean age of participants was 27.1 ± 2.45 years, with a mean gestational age of 38.6 ± 1.28 weeks and a mean weight of 68.5 ± 5.97 kg. Episiotomy was performed in 21.1% of cases, vacuum delivery in 29.3%, and macrosomia was observed in 32.5% of the participants. Stratification of episiotomy, vacuum delivery, and macrosomia by age, gestational age, and weight revealed no significant associations (p-value >0.05). The episiotomy rate was higher in women weighing ≤70 kg (24.7%) and those aged 18–30 years (23.7%). Vacuum delivery was more common in younger women (29.7%) and in those weighing >70 kg (36.7%). Conclusion: Episiotomy, vacuum delivery, and macrosomia were identified as key factors associated with intrapartum perineal tears in primigravida women. The findings suggest that variations in obstetric practices, maternal weight, and fetal characteristics play a significant role in the incidence of perineal tears. Further studies are needed to standardize practices such as episiotomy and vacuum extraction and to assess their impact on perineal trauma in diverse populations.